Comparison in vitro of cytocompatibility between fibroin and polypropylene biomaterials - Arboleda-Carvajal, Alejandro; González, Julián; Franco-Arias, Manuel Hernando; Valladares-Torres, Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This study evaluates the cell behavior of HeLa cells in vitro on fibroin and polypropylene. In order to determine cell proliferation in culture much fibroin material such as polypropylene, as the number of cells / sample was performed by the metabolic reduction of  3-(4,5- dimetiltiazol-2-ilo)-2,5-difeniltetrazol Bromide, MTT assay, using direct and indirect evidence of cytotoxicity. For direct and indirect testing of cytotoxicity in fibroin and polypropylene material, a statistical difference was found in the average number of live cells for fibroin sample regardless of the type of test (p<0.005). By the use of in vitro methods, it is shown that fibroin material has better cell behavior in terms of viability, compared with polypropylene.